Mother's Knowledge Correlation on Balanced Nutritional Behavior with Toddler Nutritional Status in Sukosewu Village, Gandusari District - Dian Puspita Anggraini; Devita Sulistiana (JOSAR (Journal of Students Academic Research), 2022)
Mother’s nutritional knowledge determines all that the children eats. Mother’s who have a good knowledge of nutrition will form a good balanced nutrition behavior for children. The behavior will affect the nutriet intake and nutritional status of children. The purpose of the study is to know the correlation mother’s knowledge and attitudes on balanced nutrition with children’s nutritional status in Desa Sukosewu village Gandusari district. This study employed Analytical Survey Research with Cross Sectional Design. The study was carried out on Juni 2022 in Sukosewu village. The collecting data mothers’s knowledge on balanced nutrition and mother’s attitude on balance nutrition used questioner, and to collect child nutritional status data using Z- score with BB/U indikator. This study involved 68 respondents. Based on bivariate analysis were tested statistically Somers’d test, the test of the correlation mother’s knowledge and attitudes on balanced nutrition with children’s nutritional status in Sukosewu village Gandusari district obtained by value p = 0.000 which shows the correlation of mother’s knowledge on balanced nutrition with children’s nutritional status in Sukosewu village Gandusari district. On the test of attitudes on balanced nutrition with children’s nutritional status in kindergartens Sukosewu village Gandusari district obtained by value p = 0.000 shows that there is correlation attitudes on balanced nutrition with children’s nutritional status in Sukosewu village Gandusari district.